Rashdan, Mahmoud Ayed. “On the Epistemological System in the Qur’an,” Year 3, Issue 10 (Fall 1418 AH/ 1997 CE), Pp. 9-43. - الرشدان, محمود عايد (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 1997)
Mahmoud Ayed Rashdan’s article treats aspects of the epistemological system, the defects and distortions that transpired in it, and what can be done to rebuild it under the guidance of the Qur’anic epistemological system. It describes the three systems: belief, knowledge, and value systems, and discusses how the Qur’an has been marginalized through the study of verses pertaining to rulings (aḥkām) only. Rashdan presents the characteristics of the Qur’anic epistemological system; how it is based on combining both reading of revelation and reading of the universe. He explains, moreover, its processes and system, its diversity and comprehensiveness of human and social phenomena, and the phenomena of the universe, signs, peoples, and nations.